2020
DOI: 10.1111/ger.12488
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial of a motivational interviewing intervention to improve oral health education amongst older adults in Philadelphia: 12‐month evaluation of non‐clinical outcomes

Abstract: ObjectivesWe conducted a trial to assess the treatment fidelity of an individual‐based oral health education intervention utilising motivational interviewing (MI) techniques and its efficacy when compared to a group‐based traditional oral health education intervention (TOHE) and a standard of care group (SC) in a sample from Philadelphia during a 12‐month follow‐up.BackgroundThere is lack of information on how different types of oral health educational interventions affect older adults on non‐clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Further, a study incorporating a MI intervention had demonstrated significant improvements in the outcome measure compared to both group education and standard care frameworks. 18 The methodological quality for the included studies varied (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Further, a study incorporating a MI intervention had demonstrated significant improvements in the outcome measure compared to both group education and standard care frameworks. 18 The methodological quality for the included studies varied (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Due to time and resource limitations, the team decided not to explore causes and interventions for patients who were uncomfortable with outpatient hydration. Several tools and interventions to help understand and improve patients’ comfort level with self-management include shared decision-making models, 20 , 21 motivational interviewing, 22 , 23 face-to-face support, 24 and supervised practice. 25 Some of these interventions could be tested and explored in future quality improvement projects.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to decrease the incidence and mortality of oral and oropharyngeal cancers include evidence-based prevention strategies such as motivational interviewing (MI) to improve oral health education 4 and HPV vaccination to prevent infections and cancers of oropharynx, tonsils, and base of the tongue in both women and men. 5 – 7 Visual and tactile screening by dentists at chairside during routine examinations for the discovery of pre- and cancerous lesions or other conditions that may benefit from treatment or close follow-up is also recommended.…”
Section: Introductionmentioning
confidence: 99%